2020
DOI: 10.3390/f11080867
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of Forest Cover Dynamics in Traditional Landscapes: Mapping Trajectories of Changes in Mountain Territories (1824–2016), on the Example of Jeleniogórska Basin, Poland

Abstract: Though on a global scale, for ecological reasons, increased forest cover is universally regarded as positive, on a local scale, the reforestation of arable land may pose threats to cultural landscapes by removing characteristic landscape features. Particularly vulnerable are marginal rural areas, e.g., mountain regions, where most traditional land use systems have survived and which are subject to the most spectacular land use change. The purpose of this article is to draw attention to the issue of the managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
1
6
1
Order By: Relevance
“…Decline was the prevalent pattern between 2002 and 2019 in the study area, lowlands, mountains, mountains protected and unprotected extents. The results are congruent with the trajectory of decline documented in the European mountains since the 1960s [11,43,44], in the neighbourhoods [45], the set of studies close to the 2020 target year [14][15][16][17], and in the study area between 2000-2010 by Regos et al [13]. Over in the area corresponding to our mountain and mountain protected extents, Regos et al [13] found a decline of 33.8% and 43.1% in grassland cover respectively, using mapped area estimates (not corrected for classification errors).…”
Section: Progress In the Conservation Of Mountain Grasslands In Southern Europe By 2020supporting
confidence: 85%
See 2 more Smart Citations
“…Decline was the prevalent pattern between 2002 and 2019 in the study area, lowlands, mountains, mountains protected and unprotected extents. The results are congruent with the trajectory of decline documented in the European mountains since the 1960s [11,43,44], in the neighbourhoods [45], the set of studies close to the 2020 target year [14][15][16][17], and in the study area between 2000-2010 by Regos et al [13]. Over in the area corresponding to our mountain and mountain protected extents, Regos et al [13] found a decline of 33.8% and 43.1% in grassland cover respectively, using mapped area estimates (not corrected for classification errors).…”
Section: Progress In the Conservation Of Mountain Grasslands In Southern Europe By 2020supporting
confidence: 85%
“…The extent of seminatural grasslands in 2015 was 49.1% less compared to 1960 due to conversion into arable land and forests [14]. Jaworek-Jakubska et al [16] in the Polish mountains indicated a 10.4% decline of grasslands between 2000-2016 in favor of forests. In contrast, a remarkable increase of managed grasslands was found between 1999-2015 (+39%) in the Carpathians [15].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In Europe, old military topographic maps were of particular use since the mid-18th century; from the 19th century onwards, they achieved a relatively solid positional accuracy by applying triangulation methods [15][16][17][18]. These maps are employed in a wide range of activities within landscape ecology, such as research into long-term changes in landscape use [19][20][21][22][23], alternatively, a part of them focus on specific types of landscape use, e.g., vineyards [24,25], forests [26,27], former water bodies [28][29][30], and certain characteristics of landscapes [31,32], expressing the knowledge that landscape representation was adapted to meet operational demands and to address the lessons learned from war experiences [33]. Old topographic maps have also found application in other fields and subsectors of science, including, but not limited, to assessing geomorphological processes and climate changes by monitoring the extent of mountain glaciers [34], estimating the impact of transport on land use [35], and combining spatial planning and population behavior in relation to transport safety [36].…”
Section: Introductionmentioning
confidence: 99%
“…Firs grow here satisfactorily at sites with different exposure, representing a broad spectrum of vegetation communities and forest habitat types [30,31]. The Sudeten fir woods, significantly reduced (by 70%-80%) as a result of intensive forest management in the 19th c. and the first half of the 20th c. (promoting spruce monocultures) e.g., [25,[38][39][40], in the years 1960-1990 were subject to the strong pressure of industrial pollution, especially SO 2 , whose average concentration in many locations exceeded 60 µg/m 3 , and periodically even 190 µg/m 3 e.g., [25,38,39,41]. These conditions, in combination with commercial activities that failed to account for fir's specific requirements, led to a situation in which its share in the forest composition was markedly lower than the initial 1% level [25].…”
Section: Introductionmentioning
confidence: 99%